An Omics Approach to Nutrient Limitation in Cupriavidus necator - Newton, Harry (2025)
As the world faces climate change, a growing population and global mass extinctions, we, as custodians, must achieve a paradigm shift across sectors to maintain our planet. As part of this effort, novel technologies must be pursued which have the potential to address these issues. The production of single cell protein (SCP) using hydrogen oxidising bacteria (HOB) holds the promise of fixing CO2 whilst alleviating food insecurity and preventing further agricultural encroachment. Realisation of the promise of this technology is reliant on its optimisation. The fermentation conditions under which HOB are grown can have a considerable impact on their product yields. Optimising growth conditions will yield an immediate benefit to such processes whilst understanding how the cell adapts to these conditions may lead to further optimisations in the future. Cupriavidus necator is a model HOB with a versatile metabolism and an amenability to genetic modification, making it an attractive CO2 fixing production chassis. Its capacity to produce both nutritionally complete protein as well as bioplastics brings the species much academic and industrial attention. This study aimed to perform a comprehensive analysis on fermentations of C. necator grown on CO2 and H2 as its sole carbon and energy sources. Preceding these fermentations, a minimal medium was designed based on the elemental composition of C. necator cells under autotrophic conditions. Continuous cultures were then undertaken using this medium under limitations of H2, O2, CO2 and NH4+ across two growth rates (1 day-1 and 3 day-1). Cell compositions were found to be highest in protein content under H2 limitation at a dilution rate of 1 day-1 however the highest protein yield based on H2 consumption was under O2 limitation at a dilution rate of 3 day-1 where 1.85 g of protein was produced per g of H2 consumed. Amino acid profiles and cell digestibility were also investigated to determine the SCP nutritional value. Cellular content of polyhydroxyalkanoates (PHAs) was also measured and NH4+ limited cells at a dilution rate of 1 day-1 were found to have 77% PHA content on average (by mass). Autotrophic production of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) was detected under H2 limitation with a 45% inclusion rate of the 3-hydroxyvalerate (3HV) monomer in the PHBV co-polymer. An omics study of the cells grown under the specified conditions was then undertaken and significant regulatory effects were seen across the proteome. A significant upregulation of hydrogenase enzymes was found under H2 limitation as well as the upregulation of the T6SS. The abundance of Rubisco was also found to be heavily dependant on the limiting nutrient, comprising 7.3% of the total proteome by mass under CO2 limitation and only 1.4% under H2 limitation (at dilution rates of 1 day-1). The data produced in this study gives an indication of the viability of C. necator as a source of SCP and gives insight into how environmental factors can impact the quality of the product. The proteomic dataset signposts points for further potential optimisation and give a resource for those hoping to model the organism. Further work is needed in assessing C. necators capacity for the autotrophic production of PHBV and in the utilisation of this omics dataset in the refinement of metabolic models.